Analisis Pengaruh Literasi Keuangan dan Financial Technology Terhadap Kinerja Keuangan Pada Usaha Mikro, Kecil, Menengah (UMKM) di Kota Metro Lampung - Zalvira Aprilia Putri; Febriyanto; Karnila Ali (Universitas Muhammadiyah Metro, 2026)
The development of Micro, Small and Medium Enterprises (MSMEs) is currently increasingly rapid. In this development, of course, MSME players are faced with various obstacles, especially related to limited capital. Apart from that, technological advances require MSME players to adapt to always keep up with developments, one of which is by utilizing financial technology. The aim of this research is to find out how financial literacy and financial technology influence the financial performance of MSMEs located in Metro City, Lampung Province. This research used an instrument in the form of a questionnaire which was distributed to 100 respondents who were MSME actors. The research method used is descriptive quantitative. The results of this research state that financial literacy and financial technology have a significant effect on the financial performance of MSMEs in Metro City, Lampung Province.